Implementasi Dan Tantangan Akuntansi Syariah Dalam Pembiayaan Musyarakah - Haris Surya Perman Permana; Nastiti Ratnadewati; M. Nur Fauzan; Nesa Abdilah; Nawal Mulqian Albaab; Mukhlishotul Jannah (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2026)
Musyarakah financing is a type of Islamic banking cooperation that emphasizes fairness, transparency, and profit sharing based on capital contributions. PSAK 106 provides guidelines for the recognition, measurement, and reporting of sharia-compliant transactions for the use of sharia accounting in this contract. The purpose of this study is to examine how the recording and reporting of musharaka financing is implemented at Bank Syariah Indonesia (BSI), identify problems, and evaluate the compliance of the practice with PSAK 106. This is a descriptive qualitative study using data collection techniques through literature studies, documentation, and analysis of previous research. The study shows that BSI has implemented PSAK 106 in general, except for the recognition of capital and income from results. However, differences in standard interpretation, limited customer financial data, information technology systems, and suboptimal field supervision all remain problems. It is hoped that this study will provide a practical overview of strengthening the application of sharia accounting in sustainable musharaka financing..